Potensi Cadangan Karbon pada Pohon dengan Penginderaan jauh di KPHP Kabupaten Sorong - Anif Farida Farida; Ponisri Ponisri (Jurnal Green Growth dan Manajemen Lingkungan, 2023)
The purpose of this study was to determine the estimation of carbon stocks based on NDVI values in the KPHP production forest of Sorong Regency. The method used is NDVI analysis to obtain estimates of carbon stocks based on field data (allometric) at the tree level. The results showed that the vegetation density in the KPHP production forest was dominated by the high class (57.40%), followed by the medium class (40.40%), and the low class (2.06%), respectively. The obtained carbon stock regression equation is y = 2.071 + 4.351 * NDVI. Carbon stock with NDVI ranges from 1,667 tons per hectare to 5,113 tons per hectare.